2019
DOI: 10.1159/000498951
|View full text |Cite
|
Sign up to set email alerts
|

First Human Use of a New Robotic-Assisted Fiber Optic Sensing Navigation System for Small Peripheral Pulmonary Nodules

Abstract: <b><i>Background:</i></b> We tested a new, investigational robotic-assisted bronchoscope system with a remotely controlled catheter to access small peripheral bronchi with real-time driving under live visualization and distal tip articulation of the catheter. The unique catheter remains stationary once located at the biopsy position. <b><i>Objectives:</i></b> The primary objectives of this study were to evaluate the safety and feasibility of a new shape-sensing r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
113
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(120 citation statements)
references
References 21 publications
3
113
1
3
Order By: Relevance
“…The newest iteration of image-guided bronchoscopy is robotic bronchoscopy, where platforms that combine advanced imaging guidance techniques with automated scopes capable of reaching the periphery of the lungs are used to access lesions previously deemed out of reach of conventional bronchoscopic techniques [91]. Initial feasibility studies are promising, even when compared to advanced techniques such as EMN bronchoscopy [91][92][93][94]. Robotic and EMN bronchoscopy have traditionally been employed as diagnostic modalities, but great interest exists in leveraging these technologies to apply therapeutic modalities for patients with peripheral nodules who cannot undergo surgical resection.…”
Section: Future Directionsmentioning
confidence: 99%
“…The newest iteration of image-guided bronchoscopy is robotic bronchoscopy, where platforms that combine advanced imaging guidance techniques with automated scopes capable of reaching the periphery of the lungs are used to access lesions previously deemed out of reach of conventional bronchoscopic techniques [91]. Initial feasibility studies are promising, even when compared to advanced techniques such as EMN bronchoscopy [91][92][93][94]. Robotic and EMN bronchoscopy have traditionally been employed as diagnostic modalities, but great interest exists in leveraging these technologies to apply therapeutic modalities for patients with peripheral nodules who cannot undergo surgical resection.…”
Section: Future Directionsmentioning
confidence: 99%
“…Fielding et al. used this system in their single‐arm prospective study and found a 96.6% success rate in reaching and obtaining samples from targeted pulmonary nodules, concluding that the robot‐assisted bronchoscope navigated safely to very small peripheral airways.…”
Section: Airway Robotsmentioning
confidence: 99%
“…The robotic components allow controlled advancement of the catheter as well as subtle directional movements in all planes at the catheter tip. The catheter has the unique property of maintaining a single position and angulation while not being advanced, with a sufficiently large working channel (2 mm) to allow passage of biopsy instruments [52,53].…”
Section: Robotic Bronchoscopymentioning
confidence: 99%